The Influence of Skills, Work Experience, and Education Levels on Employee Performance: Pengaruh Keterampilan, Pengalaman Kerja, dan Tingkat Pendidikan Terhadap Kinerja Karyawan - Sella, Kristina Nur; Ubaidillah, Hasan (Indonesian Journal of Education Methods Development, 2022)
The purpose of this study was to determine the effect of skills, work experience, and education level on employee performance at the Fifa Jaya Leather SME bag in Kedensari Village, Tanggulangin District, Sidoarjo Regency and to determine the skills, work experience, and level of education simultaneously affect employee performance at Fifa Jaya Leather bag UKM in Kedensari. The research method used in this research is quantitative. The total population and sample in this study were 47 employees using a saturated sample where the entire population was sampled. The data obtained using a questionnaire with testing using various instruments measured using the SPSS version 22 software application. The results of this study indicate that skills have a positive and significant effect on employee performance. Work experience has a positive and significant effect on employee performance. And the level of education has a negative and insignificant effect on employee performance. Simultaneously skills, work experience, and education level have a significant effect.